2020
DOI: 10.1111/nmo.13975
|View full text |Cite
|
Sign up to set email alerts
|

Functional gastrointestinal disorders are increased in joint hypermobility‐related disorders with concomitant postural orthostatic tachycardia syndrome

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 26 publications
2
22
0
2
Order By: Relevance
“…Although autonomic dysfunction in overlap hEDS/IBS has not been formally assessed, a study looking at FGID in hEDS found that out of 616 patients with hEDS, 98% had an FGID, and 37.5% had POTS. Whilst the overall prevalence of functional GI disorders did not differ between patients with hEDS with and without overlap POTS, there was an upward trend of IBS within this POTS/hEDS overlap group compared to the hEDS group without POTS (59% vs. 51%, p = .06) (Tai et al, 2020). This study suggests that symptoms in this overlap IBS/hEDS group may occur via autonomic pathways and that this is an avenue worth exploring in the comorbid IBS/hEDS group.…”
Section: Autonomic Dysfunctionmentioning
confidence: 61%
“…Although autonomic dysfunction in overlap hEDS/IBS has not been formally assessed, a study looking at FGID in hEDS found that out of 616 patients with hEDS, 98% had an FGID, and 37.5% had POTS. Whilst the overall prevalence of functional GI disorders did not differ between patients with hEDS with and without overlap POTS, there was an upward trend of IBS within this POTS/hEDS overlap group compared to the hEDS group without POTS (59% vs. 51%, p = .06) (Tai et al, 2020). This study suggests that symptoms in this overlap IBS/hEDS group may occur via autonomic pathways and that this is an avenue worth exploring in the comorbid IBS/hEDS group.…”
Section: Autonomic Dysfunctionmentioning
confidence: 61%
“…[31][32][33][34] It is frequently missed in clinical practice but may provide an important aetiological connection between fibromyalgia, ME/CFS and multiple systemic symptoms, including those described above. 35,36 Recent work indicates that symptomatic hypermobility may be present in ∼80% of fibromyalgia and ME/CFS patients, yet have only been diagnosed in one out of four cases previously. 15 Differences in connective tissue matrix (eg collagen) throughout the body could explain disparate symptoms including irritable bowel and bladder, headache and dysfunctional uterine bleeding.…”
Section: Hypermobilitymentioning
confidence: 99%
“…15,82 A recent large cross-sectional survey of adults with EDS found a high prevalence of POTS (37.5%) which was linked to a greater burden of functional GI conditions. 84 Although it is well documented that patients with JH and functional GI complaints suffer from higher somatic sensitivity and autonomic manifestations, 15 the specific neural mechanisms underlying these systemic and upper gastrointestinal complaints have not been extensively studied.…”
Section: Discussionmentioning
confidence: 99%